Topology Optimization for Aircraft Applications Using Hybrid and Multi-Material Methods for Different Component Scales - Brink, W.M. van den; Koenis, T.P.A.; Osinga, T.; Montero Sistiaga, M.L. (MDPI, 2025)
The aviation industry, responsible for a significant portion of global CO2 emissions, faces the need to transition to more sustainable aircraft. Electric aircraft driven by battery-powered propulsion and further structural weight reductions have emerged as potential solutions. This research presents structural topology optimization methods developed at the Netherlands Aerospace Centre using (1) a hybrid approach with different scales for aircraft design, from component to full-scale aircraft. Furthermore, (2) multi-material designs are being explored in combination with additive manufacturing technology. Method 1: At the full aircraft level, the study employed a preliminary design methodology that combines shell and solid elements in a 3D model utilizing Abaqus software 2023. A topology optimization was carried out with strain energy and weight as the design responses, subject to specified volume and symmetry constraints. Different aircraft configurations were investigated, including blended wing designs, with each impacting the load paths and structural performance. A start was made in translating the optimized design to actual aerospace features such as frames and Door-Surround Structures (DSS). Method 2: The ability to manufacture multi-material metal parts via additive manufacturing presents opportunities for the design of aircraft components and shows weight-saving potential. The multi-material topology optimization method is explored for a relevant aerospace wing component. The results revealed widespread possibilities for general topology optimization methods to be applied in aircraft structural design at different scales. Load paths can be identified and their integration into multi-disciplinary design optimization (MDO) is promising. Novel structural designs for blended wing aircraft can be obtained for multiple load-cases. This research addresses questions concerning the aircraft-level and component-level feasibility of optimized designs, optimization features, inertia relief, and mesh size influence. The findings show the potential to optimize battery-powered aircraft through innovative structural design, contributing to a potentially lower weight and further reductions in environmental impact. This study serves as a first step towards lightweight future electric aircraft design and underscores the importance of integrating innovative solutions to reduce the climate impact of the aviation industry.
This article belongs to the Proceedings The 14th EASN International Conference on “Innovation in Aviation & Space Towards Sustainability Today & Tomorrow”